Development of Problem-Based Interactive E-Modules to Improve Learning Outcomes of Grade V Students at SDN 1 Brondong - Apsari, Jenita Herga Putri; Agustin, Ina (Universitas Nusantara PGRI Kediri, 2025)
This study aims to develop and test the feasibility of a problem-based interactive E-Module in improving the learning outcomes of fifth-grade students in the Science subject at SDN 1 Brondong. The background to this research is the lack of student learning outcomes and the limitations of the learning media used by teachers. The approach used is the R&D (Research and Development) method that applies the ADDIE development model, which includes the stages of analyzing problems and needs, product design, product development, product implementation in elementary schools, and finally evaluation. The validation results indicate that the E-Module is considered very feasible with a score of 82% each by material and media experts, and 86% by language experts. The practicality of the media received a very positive response from teachers (96%) and students (96.8%). The effectiveness of the media is proven by an increase in learning scores with a mean N-Gain value of 0.77 or 77%, which is considered high. This electronic module is also accompanied by learning videos and problems, interactive quizzes, which are designed to encourage students to think critically and actively in learning. Based on these findings, the interactive problem-based E-Module is considered very valid, practical, and effective for use as an alternative teaching and learning media to increase the activeness and learning outcomes of students at SDN 1 Brondong.